Context-dependent effects of the renin-angiotensin-aldosterone system on blood pressure in a group of African ancestry - Scott, Leon (My University, 2012)
In groups of African ancestry, who have a high prevalence of “salt-sensitive, low-renin” hypertension, there is considerable uncertainty as to relevance of the renin-angiotensin-aldosterone system (RAAS) in the pathophysiology of primary hypertension. In the present thesis I explored the possibility that the RAAS, through interactions with environmental effects, contributes to blood pressure (BP) in this ethnic group. After excluding participants with aldosterone-to-renin ratios (ARR) above the threshold for primary aldosteronism, in 575 participants of African ancestry, I demonstrated that with adjustments for confounders, an interaction between ARR and urinary Na+/K+ (and index of salt intake obtained from 24-hour urine samples) was independently associated with BP (p<0.0001). This effect was accounted for by interactions between serum aldosterone concentrations and urinary Na+/K+ (p<0.0001), but not between plasma renin concentrations and urinary Na+/K+ (p=0.52). The interaction between ARR and urinary Na+/K+ translated into a marked difference in the relationship between urinary Na+/K+ and BP in participants above and below the median for ARR (p<0.0001 for a comparison of the relationships). Having demonstrated that circulating aldosterone concentrations may account for a substantial proportion of the relationship between salt intake and BP in this community sample, I subsequently assessed whether genetic factors contribute toward serum aldosterone concentrations. In 153 randomly selected nuclear families of African ancestry consisting of 448 participants without primary aldosteronism, with, but not without adjustments for plasma renin concentrations, independent correlations were noted for iii serum aldosterone concentrations between parents and children (p<0.05), with parent-child partial correlation coefficients being greater than those for father-mother relationships (p<0.05). Furthermore, after, but not before adjustments for plasma renin concentrations, serum aldosterone concentrations showed significant heritability (h2=0.25±0.12, p<0.02). No independent relationships between RAAS gene polymorphisms and serum aldosterone concentrations were observed. I also aimed to assess whether RAAS genes modify the relationship between cigarette smoking and BP in groups of African descent. However, as the impact of mild smoking on BP is uncertain, and in the community studied only 14.5% smoked and the majority of smokers were mild smokers (mean=7.4±4.6 cigarettes per day) in 689 randomly participants I initially assessed the relationship between smoking habits and out-of-office BP. In this regard, current smokers had higher unadjusted and multivariate adjusted 24-hour systolic/diastolic BP (SBP/DBP in mm Hg) (p<0.005-p<0.0005) than non-smokers, effects that were replicated in sex-specific groups, non-drinkers, and in the overweight and obese. Current smoking was second only to age and at least equivalent to body mass index in the quantitative impact on out-of-office BP and the risk of uncontrolled out-of-office BP was increased in smokers as compared to non-smokers. Thus, despite minimal effects on in-office BP, predominantly mild current smoking was independently associated with an appreciable proportion of out-of-office BP in a community of African ancestry. In 652 participants I subsequently assessed whether the angiotensin-converting enzyme (ACE) insertion/deletion (I/D) polymorphism accounts for the strong relationships between predominantly mild smoking and out-of-office BP. After iv appropriate adjustments, an interaction between ACE DD genotype and current cigarette smoking, or the number of cigarettes smoked per day was independently associated with 24-hour and day diastolic BP (DBP) (p<0.05-0.005). This effect translated into a relationship between smoking and out-of-office BP or the risk for uncontrolled out-of-office BP only in participants with the DD as compared to the ID + II genotypes. In conclusion therefore, I afford evidence to suggest that in groups of African ancestry, aldosterone, within ranges that cannot be accounted for by the presence of primary aldosteronism, modifies the relationship between salt intake and BP, and that genetic factors account for the variation in serum aldosterone concentrations in this group. Furthermore, I show that the ACE gene modifies the relationship between smoking and out-of-office BP and hence accounts for even predominantly mild smoking producing a marked and clinically important effect on out-of-office BP. The present thesis therefore provides further evidence in favour of an important pathophysiological role for the RAAS in contributing toward BP in groups of African ancestry.
Ph.D., Faculty of Health Sciences, University of the Witwatersrand, 2011
Keywords: blood pressure; Hypertension; Renin-Angiotensin System